The Effect of Diabetes Mellitus Gymnastics on Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus in the Work Area of the Jambi Small Health Center - Sri Mulyati; Eprina intami; Sondang Selviana Silitonga; winna Kurniasari. AZ (LP3M Universitas Muhammadiyah Tasikmalaya, 2024)
The International Diabetes Federation (IDF) estimates that people with Diabetes Mellitus in the world in 2019 will be 9.3% (483 million) people aged 20-79 years. To prevent these complications, management in Diabetes Mellitus patients is known as the four main pillars, one of which can be done with diabetes gymnastics. This type of research is quantitative research using the pre-experiment method with one group pretest and posttest. This research was conducted in the work area of the Jambi Kecil Health Center in January 2023. The population in the study were all people with Type 2 Diabetes Mellitus at the Jambi Kecil Health Center, namely 16 people. The sampling technique used in this study was total sampling. Data analysis in this study was univariate and bivariate, the statistical test used to analyze the data of the two variables was to use an independent t-test. Based on the results of the study before doing gymnastics, the average blood sugar level was 328.00 and after doing gymnastics was 203.13. There is a significant influence between Diabetes Mellitus Gymnastics on Blood Sugar Levels in Patients with Type 2 Diabetes Mellitus in the Jambi Small Health Center Working Area in 2023 with a p value of 0.000. Increase the author's knowledge and technology insights and the application of quantitative research methods in conducting research on the effect of diabetes mellitus exercises on blood sugar levels in type 2 diabetes mellitus patients.